Mesoscopic Evaluation of DNA Mismatches in PCR Primer-Target Hybridisation to Detect SARS-CoV-2 Variants of Concern - Miranda, Pâmella; Barbosa, Vivianne Basílio; Weber, Gerald (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2021: Anais do XIV Simpósio Brasileiro de Bioinformática, 2021)
Mismatches are any type of base-pairs other than AT and CG. They are an expected occurrence in PCR primer-target hybridisation and may interfere with the amplification and in some cases even prevent the detection of viruses and other types of target. Given the natural occurrence of mutations it is expected that the number of primer-target mismatches increases which may result in a larger number of false-negative PCR diagnostics. However, mismatches may equally improve the primer-target hybridisation since some types of mismatches may stabilize the helix. Only very recently have thermodynamic parameters become available that would allow the prediction of mismatch effects at buffer conditions similar to that of PCR. Here we collected primers from WHO recommendation and aligned them to the genomes of the current variants of concern (VOC): Alpha, Beta, Gamma and Delta variants. We calculated the hybridisation temperatures taking into account up to three consecutive mismatches with the new parameters. We assumed that hybridisation temperatures to mismatched alignments within a range of 5 ∘C of the non-mismatched temperature to still result in functional primers. In addition, we calculated strict and partial coverages for complete and mismatched alignments considering only single, double and triple consecutive mismatches. We found that if mismatches are taken into account, the coverage of WHO primers actually increase for VOCs and for the Delta variant it becomes 100%. This suggest that, at least for the moment, these primers should continue to be effective for the detection of VOCs.